Femicide across Europe Theory, research and prevention - Weil, Shalva; Corradi, Consuelo; Naudi, Marceline (Policy Press, 2018)
"Available Open Access under CC-BY-NC licence. Femicide, the killing of women and girls because of their gender, was until recently included in the category 'homicide', obscuring the special features of this social and gendered phenomenon. However, the majority of murders of women are perpetrated by men whom they know from family ties and are the result of intimate partner violence or so-called 'honour' killings. This book is the first one on femicide in Europe and presents the findings of a four-year project discussing various aspects of femicide. Written by leading international scholars with an interdiscplinary perspective, it looks at the prevention programmes and comparative quantitative and qualitative data collection, as well as the impact of culture. It proposes the establishment of a European Observatory on Femicide as a new direction for the future, showing the benefits of cross-national collaboration, united to prevent the murder of women and girls."